Bio-based, amorphous polyamides with tunable thermal properties. (May 2015) - van Velthoven, Juliën L.J.; Gootjes, Linda; Noordover, Bart A.J.; Meuldijk, Jan
Graphical abstract: Highlights: Both low and high T g, amorphous polymers were prepared. Fatty acid dimer and isohexide diamine were used as renewable building blocks. Degree of crystallinity can be tuned by controlling the copolyamide composition. Abstract: The aim of this work is to synthesize amorphous polyamides from renewable monomers derived from vegetable oils and sugars. By making use of the odd–even effect to hamper intermolecular hydrogen bonding, combined with either the incorporation of dimerized fatty acid monomers or isoidide diamine (IIDA) produced from fructose, the crystallization of the polyamides was suppressed considerably. Polyamides based on the dimerized fatty acid showed T g values below 10 °C. The introduction of the isoidide-based diamine enhanced the rigidity of the polymer backbone, which enabled the synthesis of amorphous polyamides with T g values up to 100 °C. For both series incomplete reaction has been observed as both end groups, i.e. amine and carboxylic acid, were detected in 1 H NMR. This results in M n values from 1 H NMR for the fatty acid-based series in the range of 4700–21, 000 g mol −1 . The M n values measured by SEC for the IIDA-based were in the range of 3000–10, 700 g mol −1 . The broad range of T g values found for these materials in combination with their relatively low molecular weights and the corresponding large amount of reactive end-groups make them suitable for application in coatings, composites, or soft-touch surfaces.